Situation Report: Poland, 22 June 1972 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Foreign Minister Olszowski in Austria Recent Developments in Polish-West German Relations Conference of Party Activists Premier Jaroszewicz in Moscow End of the Gerhard Trial Increased Polish Pressure on the Vatican